Social construction of the image of the psychologist and of the patient: the role of implicit premises - Convertini, Josephine; Luciani, Margherita (Frontiers in Psychology, 2023)
Nowadays there is a growing consideration of people's mental health through awareness programs, policy and practice promoted by international aid agencies and nongovernmental organizations. Psychologist and patient are major actors in mental health and their images are socially co-constructed. Nevertheless, there is still a lot of confusion around who "psychologists" and "patients" are or what a psychologist does. This muddle may underline stereotypes and broadly speaking stigma related to mental health (World Health Organization, 2022). Therefore, to confront directly the ideas of "psychologist" and "patient" could be a little step in challenging stereotypes and in making order in the panorama of mental health. In our work, we focus on the implicit contextual premises that shape particular framings around which the images of the psychologist and of the patient are socially and culturally co-constructed. In order to reach this goal, we have investigated the discourses and the multiple points of view behind the social image of the psychologist and of the patient gained from different sources or contextual domains: psychology online forums, university websites and an online survey. From a methodological perspective and according to the pragma-dialectical approach, we have identified all the different standpoints and arguments related to the various conceptions of the psychologist and of the patient. We have made explicit the implicit premises that lay behind each argumentative inference via the Argumentum Model of Topics. Based on these analyses, we have reconstructed the distinct framings at stake in the different contextual domains. The findings show that implicit contextual premises have a huge power in constructing stigmatization in the idea that lay people have towards the image of the psychologist and of the patient. In particular, we have observed that the more the contextual domain is defined, the more institutional premises dominate over individual one; on the contrary, in informal contextual domains heterogenous individual premises are prominent. Our paper underlines that it is only by substituting old implicit premises with new unimagined ones that we can change subjacent contextual premises at the very core of stigma and prototypical world's images.